Plasmodium berghei Kinesin-5 Associates With the Spindle Apparatus During Cell Division and Is Important for Efficient Production of Infectious Sporozoites - Zeeshan, Mohammad; Brady, Declan; Stanway, Rebecca R.; Moores, Carolyn A.; Holder, Anthony A.; Tewari, Rita (Frontiers in Cellular and Infection Microbiology, 2020)
Kinesin-5 motors play essential roles in spindle apparatus assembly during cell division, by generating forces to establish and maintain the spindle bipolarity essential for proper chromosome segregation. Kinesin-5 is largely conserved structurally and functionally in model eukaryotes, but its role is unknown in the Plasmodium parasite, an evolutionarily divergent organism with several atypical features of both mitotic and meiotic cell division. We have investigated the function and subcellular location of kinesin-5 during cell division throughout the Plasmodium berghei life cycle. Deletion of kinesin-5 had little visible effect at any proliferative stage except sporozoite production in oocysts, resulting in a significant decrease in the number of motile sporozoites in mosquito salivary glands, which were able to infect a new vertebrate host. Live-cell imaging showed kinesin-5-GFP located on the spindle and at spindle poles during both atypical mitosis and meiosis. Fixed-cell immunofluorescence assays revealed kinesin-5 co-localized with α-tubulin and centrin-2 and a partial overlap with kinetochore marker NDC80 during early blood stage schizogony. Dual-color live-cell imaging showed that kinesin-5 is closely associated with NDC80 during male gametogony, but not with kinesin-8B, a marker of the basal body and axonemes of the forming flagella. Treatment of gametocytes with microtubule-specific inhibitors confirmed kinesin-5 association with nuclear spindles and not cytoplasmic axonemal microtubules. Altogether, our results demonstrate that kinesin-5 is associated with the spindle apparatus, expressed in proliferating parasite stages, and important for efficient production of infectious sporozoites.